Hydrogen generation by hydrolysis of alkaline sodium borohydride using a cobalt–zinc–boron/graphene nanocomposite treated with sodium hydroxide. (22nd March 2015) - Xiang, Cuili; Jiang, Dadi; She, Zhe; Zou, Yongjin; Chu, Hailiang; Qiu, Shujun; Zhang, Huanzhi; Xu, Fen; Tang, Chengying; Sun, Lixian
Abstract A Co–Zn–B/graphene nanocomposite was prepared by in situ reduction of cobalt and zinc salts on the surface of graphene (GP), and its catalytic performance in hydrogen generation (HG) by hydrolysis of NaBH4 was investigated. This composite exhibited excellent catalytic properties and great promise for real-world applications in HG and hydrogen storage. Characterization using X-ray diffraction, scanning electron microscopy, and Brunauer–Emmett–Teller (BET) adsorption analysis showed Co–Zn–B nanoparticles attached to the GP surface. The catalytic activity was further improved by treating the nanocomposite with NaOH to remove zinc from the composite matrix and increase the active surface area. The BET measurements showed the specific area of the treated material increasing from 86.4 to 120.2 m2/g. The effects of temperature, NaBH4 concentration, and NaOH concentration on HG were investigated. The measured HG rate was 2180 mL/(min·g) at 30 °C in a 5 wt.% NaOH + 3 wt.% NaBH4 solution, much higher than rates obtained for unsupported Co–Zn–B catalysts. The stability of the fabricated composite catalyst was also explored.